PENGARUH PENGGUNAAN MODUL PRAKTIKUM DIGITAL DALAM PEMBELAJARAN IPA UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR KREATIF MAHASISWA PGSD (JS (JURNAL SEKOLAH), 2025)
Abstract: The purpose of this study was to determine the effect of the use of digital practicum modules on the creative thinking abilities of primary teacher education students in science learning in Elementary Schools. This study used a quantitative research type with an experimental method in the form of a quasi-experimental design. The quasi-experimental design applied was a nonequivalent control group design. The data collection techniques used were interviews, observations, tests, and documentation. The sample in this study were primary teacher education students who took science learning courses in Elementary Schools, where sampling was carried out by purposive sampling so that classes H and I PGSD 2023 were obtained as experimental and control classes. The instruments used in this study were interview sheets, implementation observation sheets, essay tests and documentation sheets. The data analysis technique used was a statistical test in the form of an Independent Sample T-Test using SPSS 30. The results of this study indicate that the creative thinking abilities using digital practicum modules are higher than the creative thinking abilities of students without using digital practicum modules. The Independent Sample T-Test test showed Sig. (2-tailed)